Simulated Coronal Mass Ejections on a Young Solar-type Star and the Associated Instantaneous Angular Momentum Loss - Yu Xu; Julián D. Alvarado-Gómez; Hui Tian; Katja Poppenhäger; Gustavo Guerrero; Xianyu Liu (The Astrophysical Journal, 2024)
Coronal mass ejections (CMEs) on stars can change the stars’ magnetic field configurations and mass-loss rates during the eruption and propagation and therefore, may affect the stars’ rotation properties on long timescales. The dynamics of stellar CMEs and their influence on the stellar angular momentum loss rate are not yet well understood. In order to start investigating these CME-related aspects on other stars, we conducted a series of magnetohydrodynamic simulations of CMEs on a solar-type star of moderate activity levels. The propagation and evolution of the CMEs were traced in the three-dimensional outputs and the temporal evolution of their dynamic properties (such as masses, velocities, and kinetic energies) were determined. The simulated stellar CMEs are more massive and energetic than their solar analog, which is a result of the stronger magnetic field on the surface of the simulated star than that of the Sun. The simulated CMEs display masses ranging from ∼10 ^16 to ∼10 ^18 g and kinetic energies from ∼10 ^31 to ∼10 ^33 erg. We also investigated the instantaneous influence of the CMEs on the star’s angular momentum loss rate. Our results suggest that angular momentum can either be added to or removed from the star during the evolution of CME events. We found a positive correlation between the amplitude of the angular momentum loss rate variation and the CME’s kinetic energy as well as mass, suggesting that more energetic/massive CMEs have a higher possibility to add angular momentum to the star.